Abnormal Olfaction in Parkinson’s Disease Is Related to Faster Disease Progression - Sara Cavaco; Alexandra Gonçalves; Alexandre Mendes; Nuno Vila-Chã; Inês Moreira; Joana Fernandes; Joana Damásio; Armando Teixeira-Pinto; António Bastos Lima (Behavioural Neurology)
Introduction. A possible association between olfactory dysfunction and Parkinson’s disease (PD) severity has been a topic of contention for the past 40 years. Conflicting reports may be partially explained by procedural differences in olfactory assessment and motor symptom evaluation. Methods. One hundred and sixty-six nondemented PD patients performed the Brief-Smell Identification Test and test scores below the estimated 20th percentile as a function of sex, age, and education (i.e., 80% specificity) were considered demographically abnormal. Patients underwent motor examination after 12 h without antiparkinsonian medication. Results. Eighty-two percent of PD patients had abnormal olfaction. Abnormal performance on the Brief-Smell Identification Test was associated with higher disease severity (i.e., Hoehn and Yahr, Unified Parkinson’s Disease Rating Scale-III, Freezing of Gait questionnaire, and levodopa equivalent dose), even when disease duration was taken into account. Conclusions. Abnormal olfaction in PD is associated with increased severity and faster disease progression.